An Economic Analysis of Mulberry and Cocoon Production in North Eastern Karnataka - G. N., Anil Kumar; G. V, Mohith Kumar; N. L., Vijaya; B. S, Reddy; G. V., Venkataravana Nayaka (International Journal of Bio-resource and Stress Management, 2022)
The present study is an attempt to assess the silkworm cocoon production and its profitability in North Eastern Karnataka region, India through structured survey during June–September, 2018. The multistage random sampling technique was adopted in designing sampling frame. In the first stage, three districts namely Ballari, Kalaburagi and Raichur districts were selected based on the highest area under mulberry crop. In the second stage two taluks were selected based on the potentiality and highest area under mulberry crop. In the third stage, 10 farmers from selected taluks of the districts were selected randomly in view of spread out of sericulture farmers in different villages. Total sample size of sericulture farmers were 60 respondents. However, 15 market intermediaries representing 5 respondents each from the selected districts constituting village trader and reeler’s were chosen randomly and interviewed personally to elicit required information with the help of well-structured and pre-tested schedule. The human labour usage in establishment of mulberry garden was highest in Kalaburagi (53.25 mandays) compared to Raichur (50.30 mandays) and Ballari (46.80 mandays). The variable cost incurred by sericulture farmers was more than 81% of the total cost of cultivation of mulberry. However, the expenditure on human labour (35.97%) was the major constituent of the total cost. The net returns realised by silk cocoon producing farmers was ` 55,819 300 DFL-1. The extent of net returns realised was highest in Kalaburagi (` 58,708 300 DFL-1) district compared to Raichur (` 54,726) and Ballari (` 54,025) districts.